Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1042/0264-6021:3610443
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the synaptic protein PICK1 (protein interacting with C kinase 1) with the non-voltage gated sodium channels BNC1 (brain Na+ channel 1) and ASIC (acid-sensing ion channel)

Abstract: Neuronal members of the degenerin/epithelial Na(+) channel (DEG/ENaC) family of cation channels include the mammalian brain Na(+) channel 1 (BNC1), acid-sensing ion channel (ASIC) and dorsal-root acid-sensing ion channel (DRASIC). Their response to acidic pH, their sequence similarity to nematode proteins involved in mechanotransduction and their modulation by neuropeptides suggest that they may function as receptors for a number of different stimuli. Using the yeast two-hybrid assay, we found that the PDZ dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
118
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(130 citation statements)
references
References 48 publications
11
118
1
Order By: Relevance
“…Indeed, PICK1 is known to target the activated form of PKC␣ to several transmembrane proteins for phosphorylation in a PDZ-dependent manner, which, in turn, alters their trafficking and functional regulation (Xia et al, 1999;Baron et al, 2002a;Williams et al, 2003). For instance, PICK1 binds to the C-termini of several isoforms of the ASIC family of proton-gated ion channels (ASIC1a, 2a, and 2b) via its PDZ domain (Duggan et al, 2002;Hruska-Hageman et al, 2002). Further, PICK1 is believed to target activated PKC␣ to ASIC2a, thereby leading to the phosphorylation of the channel in its cytoplasmic tail and to the potentiation of ASIC2a currents (Baron et al, 2002a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, PICK1 is known to target the activated form of PKC␣ to several transmembrane proteins for phosphorylation in a PDZ-dependent manner, which, in turn, alters their trafficking and functional regulation (Xia et al, 1999;Baron et al, 2002a;Williams et al, 2003). For instance, PICK1 binds to the C-termini of several isoforms of the ASIC family of proton-gated ion channels (ASIC1a, 2a, and 2b) via its PDZ domain (Duggan et al, 2002;Hruska-Hageman et al, 2002). Further, PICK1 is believed to target activated PKC␣ to ASIC2a, thereby leading to the phosphorylation of the channel in its cytoplasmic tail and to the potentiation of ASIC2a currents (Baron et al, 2002a).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, PICK1 can dimerize via its central coiled-coil motif and thereby promote protein complex formation between its binding partners. One such PICK1-associated protein is the proton-gated ion channel ASIC2a, a mammalian member of the degenerin/epithelial Na ϩ channel (DEG/ ENaC) superfamily (Duggan et al, 2002;Hruska-Hageman et al, 2002). Interestingly, Baron et al (2002a) reported that activation of PKC strongly potentiates ASIC2a currents in a PICK1-dependent manner.…”
Section: Parkin Suppresses Pick1-mediated Potentiation Of Asic2a Currmentioning
confidence: 99%
“…ASIC1a has similar function in both cell types (10). For measurements of [Ca 2ϩ ] c , COS-7 cells were transfected by electroporation (26) and plated on collagen-coated glass cover slips. For patch-clamp studies and measurements of lactate dehydrogenase (LDH) release, Chinese hamster ovary cells, and COS-7 cells, respectively, were transfected with TransFast Lipid Reagent (Promega) and cultured on 35-mm Petri dishes.…”
Section: Methodsmentioning
confidence: 99%
“…In particular there has been a lot of interest in PICK1 since it was originally identified as an interactor for PKCa (Staudinger et al 1995(Staudinger et al , 1997. In addition, to PKCa and GluR2, PICK1 also interacts with a number of other proteins including mGluR7 (Boudin et al 2000;Dev et al 2000;El Far et al 2000), non-voltage-gated Na 1 channels (Baron et al 2002;Duggan et al 2002;Hruska-Hageman et al 2002) and ephrin receptors (Torres et al 1998). Although PICK1 contains only a single PDZ domain, it can also dimerize via a coiled-coil domain (Perez et al 2001) providing the possibility that PICK1 dimers could target other proteins such as PKCa to AMPARs.…”
Section: The Pdz Sitementioning
confidence: 99%